2015
DOI: 10.1007/s00253-015-6752-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial lipid production by oleaginous Rhodococci cultured in lignocellulosic autohydrolysates

Abstract: Metabolic synthesis of single cell oils (SCOs) for biodiesel application by heterotrophic oleaginous microorganisms is being hampered by the high cost of culture media. This study investigated the possibility of using loblolly pine and sweetgum autohydrolysates as economic feedstocks for microbial lipid production by oleaginous Rhodococcus opacus (R. opacus) PD630 and DSM 1069. Results revealed that when the substrates were detoxified by the removal of inhibitors (such as HMF-hydroxymethyl-furfural), the two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…These biooils are most commonly used as a replacement for petroleum fuels but they can be also served as feedstock for production of a wide range of value-added products. For instance, lignin-derived phenolics can be converted into aromatic chemicals by hydrogenation [69], and carbohydrates are utilized for catalytic production of hydrogen or consumed in fermentation [70].…”
Section: Thermochemicalmentioning
confidence: 99%
“…These biooils are most commonly used as a replacement for petroleum fuels but they can be also served as feedstock for production of a wide range of value-added products. For instance, lignin-derived phenolics can be converted into aromatic chemicals by hydrogenation [69], and carbohydrates are utilized for catalytic production of hydrogen or consumed in fermentation [70].…”
Section: Thermochemicalmentioning
confidence: 99%
“…Though engineered algae and yeast are prominent in the field, the oleaginous soil bacteria in the family Rhodococcus is an emerging candidate for study due to a broader threshold of suitable nutrients and cultivation conditions (Alvarez et al 2000 ; Gomez et al 2016 ; Salvachúa et al 2015 ). In recent years, Rhodococcus opacus ( R. opacus ) strains DSM 1069 and PD630 have been investigated for their ability to accumulate significant amounts of intracellular single cell oils (Kosa and Ragauskas 2011 , 2012 , 2013 ; Wei et al 2015a , b , c ). For example, R. opacus PD630 has been shown to exhibit oleaginicity ~ 80% on a cell dry weight basis (CDW) when glucose was utilized as a carbon source under nitrogen-limited conditions (Alvarez et al 2000 ; Alvarez and Steinbuechel 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, effluent fractions are discarded as industrial wastewater but here it was shown to be a viable feedstock for the production of microbial lipids possibly due to the increased solubility of lignin compounds. Wei showed that oleaginicity can be improved (28%) when substrates are detoxified by the removal of inhibitors such as hydroxymethyl-furfural [70] (Table 1, #3). Fermentations of Kraft lignin from black liquor by R. opacus also resulted in poor lipid titers (<0.01 mg/ml) and strain oleaginicity [71] suggesting that pretreatments were necessary to improve the properties of Kraft lignin.…”
Section: Lignocellulosic Biomass Pretreatment Strategiesmentioning
confidence: 99%
“…R. opacus can metabolize and degrade aromatic compounds found in lignocellulosic biomass [64] and accumulate intracellular single cell oils [54][55][56][57][58][59]. Rhodococcus strains have been engineered to express enzymes to degrade cellulose [65] and xylose [66].…”
Section: Fermentations Using Different Lignin Substrates or Pretreatmmentioning
confidence: 99%
See 1 more Smart Citation